A case of diquat poisoning in pigs - Zuzana Siroka; Martin Svoboda; Zdenka Svobodova; Ivan Nagl (Veterinární Medicína, 2019)
Diquat is a bipyridyl compound which belongs to the group of herbicides. Its activity is based on the liberation of the superoxide anion radical and, subsequently, hydrogen peroxide, leading to tissue destruction by oxidative stress. Acute poisoning is associated with high mortality within several hours to a few days. The reported case of poisoning occurred on a commercial farm. The fattening pigs of the Landrace and Large White breeds were affected. The pigs were kept on a deep litter. Reglone (active ingredient diquat dibromide, 200 g/l) was used on the farm fields to desiccate the clover crop. The dry clover straw was harvested and stored for approximately a month and then used as a litter. In total, 50 pigs were affected. The onset of the poisoning was very fast. Within eight hours after the litter administration, 20 animals died. The only clinical sign seen was severe haemorrhagic dermatitis. The pathological examination revealed acute superficial haemorrhagic dermatitis on the belly, the snout and the ears of the affected pigs. Hyperaemia of the tonsils, pharynx and oesophagus was diagnosed, as well as a pronounced hyperaemia of the stomach fundus. In the distal part of the trachea, there was a dense, white foam. The lungs were congested, with focal emphysema. The liver was slightly hyperaemic. The histological examination revealed a massive haemostasis in liver and diffuse acute polymorphonuclear hepatitis. The other organs were without changes. The examination revealed acute poisoning caused by the large body surface areas contacting with a toxic substance. The pigs that survived were immediately removed to a non-contaminated area. The changes on their skin were not so extensive compared to the dead ones. Within 5-7 days after the exposure to diquat, the skin lesions healed.